Design and Build a Drum Collector Using a Stepper Motor Arduino Based on Nanofiber Spinning Machine (Electrospinning) - Wulan Oktaviani; Sri Wahyu Suciyati; Gurum Ahmad Pauzi; Junaidi Junaidi (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
An Arduino-based stepper motor was used to create a nanofiber spinning machine. The hardware for this tool includes an Arduino Mega module, a 4x4 keypad, a TM1637 type seven-segment display, and L298N type stepper motor driver, a 17Hs4401 type stepper motor, a Pushbutton, and an ultrasonic sensor. The software utilized is the Arduino IDE, which is written in C. This tool's operating premise is that the Arduino processes input from the Keypad, and then the Stepper Motor Driver drives the stepper motor, which moves the collection drum up and down. The results of reading the tool will be presented in the seven segments in the form of RPM, altitude, and time. The tool has a height range of 1-10 cm, an RPM range of 10-100 RPM, and a time range of 1 minute to 1 hour. According to the test results, the tool has 99.8 percent accuracy at RPM, 99.92 percent accuracy at the time, and 97.89 percent accuracy at altitude.